2011
DOI: 10.1111/j.1755-5922.2011.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of the Central Antihypertensive Agent, Moxonidine

Abstract: SUMMARYThe sympathetic nervous system plays a central role in the pathophysiology not only of hypertension and other cardiovascular diseases but also metabolic disorders including disturbances of glucose and lipid homeostasis. A centrally acting sympathetic agent is therefore attractive not only for lowering blood pressure, but also intervening with multiple disease processes. Older agents such as clonidine and guanabenz have numerous side effects, including sedation and dry mouth that limit their acceptabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 106 publications
(137 reference statements)
1
34
0
12
Order By: Relevance
“…Moxonidine reduces the levels of central sympathetic tone, leading to significant hemodynamic and metabolic effects, with minimal stimulation of α-2 adrenergic receptors, resulting in marked reduction in undesired effects compared with older centrally acting antihypertensives, including clonidine. 27 Although moxonidine is an effective antihypertensive with favorable hemodynamic and metabolic effects, 27 in the Moxonidine in Congestive Heart Failure trial, it was found to have a deleterious effect in patients with heart failure and an ejection fraction of <35% 28 (thus the exclusion of heart failure patients from the present study). The use of moxonidine in the patient population of the present study was not associated with any …”
Section: Discussionmentioning
confidence: 96%
“…Moxonidine reduces the levels of central sympathetic tone, leading to significant hemodynamic and metabolic effects, with minimal stimulation of α-2 adrenergic receptors, resulting in marked reduction in undesired effects compared with older centrally acting antihypertensives, including clonidine. 27 Although moxonidine is an effective antihypertensive with favorable hemodynamic and metabolic effects, 27 in the Moxonidine in Congestive Heart Failure trial, it was found to have a deleterious effect in patients with heart failure and an ejection fraction of <35% 28 (thus the exclusion of heart failure patients from the present study). The use of moxonidine in the patient population of the present study was not associated with any …”
Section: Discussionmentioning
confidence: 96%
“…2 and 8 hours in case of moxonidine and rilmenidine, respectively) (Edwards et al 2012;Verbeuren et al 1990), it might be argued that once daily administration of these agents is not enough to explore their potential anti-or pro-inflammatory actions. Although short plasma half-life does not necessarily mean short duration of action, for example, the antihypertensive action of both moxonidine and rilmenidine lasts 12-24 hours in humans (Edwards et al 2012;Verbeuren et al 1990), we changed the treatment regimen and injected them twice daily to test, whether it would enhance their potential intestinal effects. Rilmenidine, AGN 192403 and efaroxan still failed to influence the macroscopic signs of DSS-evoked colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The I1-IR subtype, which displays high affinity for 2-aminoimidazolines such as clonidine, and medium affinity for imidazolines such as idazoxan (Dardonville and Rozas, 2004), has attracted particular attention due to its role in the regulation of cardiovascular functions (Bousquet et al 1984(Bousquet et al , 2003. The concept that I1-IRs localized in the rostral ventrolateral medulla mediate or at least contribute to the hypotensive effect of clonidine and its structural analogs, whereas alpha2-adrenoceptors mediate the adverse effects (sedation, dry mouth) has led to the development of moxonidine and rilmenidine, which possess higher affinity for I1-IRs than for alpha2-adrenoceptors and used world-wide as antihypertensive agents (Bousquet et al 2003;Edwards et al 2012;Verbeuren et al 1990). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fármacos anti-hipertensivos de ação central, classificados como agonistas adrenérgicos α 2 e imidazólicos, como a moxonidina, clonidina e rilmenidina, são eficazes no tratamento da hipertensão (EDWARDS et al, 2012;ERNSBERGER et al, 1993). Parece haver um consenso geral de que o principal local de ação desses fármacos seriam os neurônios pré-motores simpáticos da região RVL/C1 (GUYENET, 1997;PUNNEN et al, 1987;REIS, 1996).…”
Section: Envolvimento Da Região Comissural Do Nts Sobre Os Efeitos Caunclassified